Formulation and Evaluation of Grape Seed Oil (Vitis Vinifera, L) Facial Cream with Variations in The Concentration of Stearic Acid as an Emulsifier - Yusuf Supriadi; Nurbik Khoirin (The Indonesian Institute of Science and Technology Research, 2022)
Ageing is a complex biological process resulting from intrinsic ageing and extrinsic ageing. The most influential factor in ageing is free radicals because they can cause oxidative stress, which plays an essential role in the ageing process. Oligomeric proanthocyanidins (OPC) in grapeseed oil have the highest antioxidant effect against free radicals. These antioxidants are used in cosmetic products to maximize the treatment of ageing. This study aims to optimize the formula for grape seed oil cream by varying the concentration of stearic acid as an emulsifier. Grape seed oil is formulated into cream preparations which are divided into three formulas, namely formula one (F1), which uses 10% stearic acid concentration, formula two (F2) 12% stearic acid concentration, and formula three (F3) 14% stearic acid concentration. Determination of optimum stability and formula is obtained from the evaluation of cream preparations, including organoleptic, physical homogeneity, pH, dispersion, viscosity, and emulsion type tests. The results showed that the concentration of stearic acid emulsifiers affected the spreadability and viscosity. And does not affect the pH, homogeneity, and type of emulsion.